(untitled) (Al-Qamar, 2021)
There are various modern trend in the subcontinent regarding Metaphysical issues. This article presents a study of the thoughts of the scholars on various metaphysical issues and sees how the critics of modern trends are approaching them. Whether they stay close to the real Islamic point of view in criticizing modernists or not. This analysis shows that the ideology of the modernists on the subject under consideration is not correct and what the critics have criticized on them is accurate.